Want to Inspire Science Students to Consider a Research Career? Host a Scientist in Your Classroom - Patricia J. Baynham (American Society for Microbiology, 2010)
Most biology students have limited exposure to research since this is not a public activity and the pace of science does not lend itself to television dramatization. In contrast, medicine is the subject of numerous TV shows, and students’ experience visiting doctors may lead them to think they want to become physicians. One effective way to encourage these students to consider a research career is to invite engaging scientists to speak about their career paths and lives during class. Students are most likely to be influenced by people they consider to be like themselves. While this method is well-suited to a lecture format where the scientist can address a larger audience, the laboratory would also be appropriate.